Laser remelting of CoCrFeNiTi high entropy alloy coatings fabricated by directed energy deposition: Effects of remelting laser power. (February 2023) - Li, Yunze; Hu, Yingbin; Zhang, Dongzhe; Cong, Weilong
Highlights: DED with remelting process fabricated CoCrFeNiTi HEA coatings. Different molten pool thermal characteristics due to the laser remelting process. The phase and microstructure transform under different remelting laser power. Extremely increased hardness and wear resistance due to laser remelting process. Abstract: Owing to their superior mechanical properties of high hardness, wear resistance, and corrosion resistance, CoCrFeNiTi high entropy alloys (HEAs) attracted the attention of researchers to use as coating materials for titanium (Ti) and its alloys. Directed energy deposition (DED) has the potential to combine both the fabrication process and the laser remelting process (implemented by double laser scanning) using the same equipment set-up. With high energy density and rapid cooling rate, combining DED and laser remelting is considered an effective method to enhance solid solution strengthening effects and element segregation of CoCrFeNiTi HEA coatings, thus being able to affect HEA coatings' phase constitutions, microstructure, and mechanical properties. To date, there are no reported publications on the deposition of CoCrFeNiTi HEA coatings via the combination of DED and laser remelting process. In addition, the investigation of the effects of remelting laser power is still lacking. To fill these gaps, the relationships among the levels of remelting laser power, molten pool properties, microstructure, and mechanical properties of CoCrFeNiTi HEA coatings are built by DED with the laser remelting process in this investigation. When the remelting laser power is higher than 225 W (75 % of the laser power in the DED process), the three-phase microstructure changes to a two-phase microstructure. The higher molten pool temperature, lower cooling rate, and secondary solidification induced by a relatively high remelting laser power can enhance the solid solution strengthening effects and promote the precipitation of the high-hardness Χ phase and Laves phase. After the 300 W laser remelting process, the highest average microhardness of the coatings is obtained as 916 HV1.0, which is 65 % higher than that of the coatings without laser remelting process. The best wear resistance is observed in the coatings with 225 W remelting laser power instead of 300 W remelting laser power since the high content of brittle phase caused by high remelting laser power could promote the formation of abrasive particles during the dry sliding tests.